Developing the skill of writing in a mind map style: تنمية مهارة الكتابة بأسلوب الخريطة الذهنية - M. Abdillah Subhin (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
This article discusses the latest experimental studies showing that, common language can increase mental capacity or intelligence in humans, so that it can further improve how to speak with evidence that he has found the percentage of deaf intelligent and stupid is lower than normal humans, the first early education and dependence on the acquisition of knowledge and experience through linguistic friction that is always increasing can be accepted by IQ like a normal child's mentality.